Transcatheter Mitral Valve-in-Valve Implantations Using Inverted J-Valve - Liu, Lulu; Xiao, Bowen; Wu, Binggang; Guo, Yingqiang (Frontiers in Cardiovascular Medicine, 2022)
Background: As bioprosthetic valves are being widely used, the incidence of structural valve deterioration increases, as well as the need for reoperation. Transcatheter mitral valve-in-valve implantations are being increasingly adopted as an alternative to redo-surgical mitral replacement for patients with high surgical risks. This study reports a series of transcatheter mitral valve-in-valve implantations using inverted J-valves. Methods: From April 2019 to September 2021, 17 symptomatic high-risk patients with mitral bioprosthetic valve dysfunction underwent transapical transcatheter mitral valve-in-valve implantations using inverted J-valves at our institution. Results: The median age was 70 years, with 76.5% being female. The median Society of Thoracic Surgeons predicted risk of mortality (STS PROM) was 17.2% (8.7%-82.24%). All patients had successful transapical transcatheter mitral valve-in-valve implantations except one intraoperative death due to left ventricle rupture. Four patients underwent simultaneous transcatheter aortic valve implantation, two of which had valve-in-valve transcatheter aortic valve implantation. There was no major complication except one case of bleeding. 30-day mortality was 11.8% (2/17), and 90-days mortality was 23.5% (4/17). Percentages of patients with New York Heart Association class III/IV symptoms decreased from 100% (17/17) to 20% (3/15) at 30-days. Median mitral inflow velocity was 1.95 mm/s at 30 days, compared to 2.7 mm/s at baseline. Median mitral valve effective orifice area increases from 1.5 mm at baseline to 1.85 mm at 30 days. Conclusions: Transcatheter transapical valve-in-valve implantations with J-valve can be a plausible solution to failed mitral bioprosthesis with acceptable results for high-risk patients.